Optimization of microwave-assisted extraction of antihepatotoxic triterpenoid from actinidia deliciosa root and its comparison with conventional extraction methods - Bai, Xinpeng (Array, 2007)
A simple and rapid microwave-assisted extraction (MAE) procedure has been developed and optimized for extracting triterpenoids (TTP) from the Actinidia deliciosa root. Several variables that could potentially affect the extraction efficiency, namely extraction time (min), ethanol fraction (%), liquid:solid ratio (volume per mass) and microwave power (W) have been optimized by means of response surface methodology (RSM). The results suggest that ethanol concentration and microwave power were statistically most significant factors. The optimal conditions were determined and three-dimensional response surfaces were plotted from the mathematical models. The optimum conditions were ethanol fraction 72.67 %, microwave power 362.12 W, liquid:solid ratio (volume per mass) 15:1 and extraction time 30 min. Under the optimum operating conditions, the percentage of extracted TTP was 84.96 %, and MAE showed significantly higher recoveries than those obtained by the conventional extraction methods (ultrasonic and reflux extraction). In addition, a drastic reduction of the extraction time (30 min vs. 8 h) and solvent consumption (15 vs. 30) was achieved, comparable with that provided by the reflux extraction as a reference method